2017
DOI: 10.3390/en10081223
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Heavy Fuel Oil Spray and Combustion under Low-Speed Marine Engine-Like Conditions

Abstract: On account of their high power, thermal efficiency, good reliability, safety, and durability, low-speed two-stroke marine diesel engines are used as the main drive devices for large fuel and cargo ships. Most marine engines use heavy fuel oil (HFO) as the primary fuel, however, the physical and chemical characteristics of HFO are not clear because of its complex thermophysical properties. The present study was conducted to investigate the effects of fuel properties on the spray and combustion characteristics u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To study the effect of changes in liquid viscosity on the spray characteristics the experiments were repeated with water and water-glycerol solutions [37,38]. This was done to reproduce the viscosities of some of the fuels used in the boiler [39], or achievable with a fuel preheating system [40]. The solutions were designed using the viscosity data found in literature [41].…”
Section: The Setupmentioning
confidence: 99%
“…To study the effect of changes in liquid viscosity on the spray characteristics the experiments were repeated with water and water-glycerol solutions [37,38]. This was done to reproduce the viscosities of some of the fuels used in the boiler [39], or achievable with a fuel preheating system [40]. The solutions were designed using the viscosity data found in literature [41].…”
Section: The Setupmentioning
confidence: 99%
“…Since slow-speed diesel engines are fueled with HFO (heavy fuel oil), the properties for this fuel are introduced in the model. HFO has higher density, viscosity, surface tension, and evaporation heat than automotive diesel fuel, which results in bigger droplets, longer spray penetration, and slower heat release [27,28]. The fuel properties are dependent on temperature and pressure, so the properties were introduced to the code in the form of functions.…”
Section: Enginementioning
confidence: 99%
“…Altaher et al observed that the higher air velocity inside the turbine chamber caused smaller SMDs, which improved the mixing and atomizing of fuel injection [22]. Other interesting works including SMD analysis were realized by Park et al [23] and Zhou et al [24]. Valuable research work on spraying and mixture formation with the aid of optical measurement instrumentation was presented by Tzanetakis et al [25] and Park et al [26].…”
Section: Introductionmentioning
confidence: 99%